Religious dicourses justifying gender violence in a group of women from Upala: sacrifice, guilt and spiritualities - Argüello, Brenda Jiménez (2023)
This work investigates the violence suffered by five women from Upala, located in Costa Rica. It analyzes aspects of violence that they are living from spaces such as culture, the family and religious institutions. For this reason, notions that are deci- sive in the legitimization of this violence are examined, such as sacrifice, guilt, their liberator spiritualities and the vision of God as who solves problems. According to this, information recollection tools were used to qualitative investigation such as semi-structured interviews. In this way, it is evident how cultural violence is legitimized through imaginaries and religious discourses that come to have an impact on the lives of these women by justifying many of the situations of violence they live and contribute to the construction of subjectivities rooted to passivity, obedience, sacrifice and dedication. In addition, it shows how analyzing oppressive religious discourses can be favorable to the position that women have in situations of violence that are based on a religious language immersed in the cultural. In such manner, the text allows to know from the life stories of these five women who are part of a female group that has been victim of violence, the impact of a society that maintains structures that violate women and that are sustained through religious imperatives.